TESTING THE FLUIDITY OF 65Г STEEL ALLOY - Saidmakhamadov Nosir Muysinalievich; Abdullaev Kamol Khakimovich; Mamashaev Muzaffar Abdumalikovich; Babaev Narimon Otabaevich; Usmanov Bobirjon Bakhodirjanovich (Modern American Journals, 2025)
In this article, the effect of adding different amounts of aluminum to a low-carbon 65Г steel alloy on its fluidity was investigated. The research was carried out using the induction melting method. During the experiments, aluminum was added to the molten metal in amounts of 0.2%, 0.4%, 0.6%, and 0.8%. Based on U-shaped sand-clay mold samples, the degree of fluidity was determined by measuring the casting length obtained for each aluminum content. The results showed that the addition of aluminum increases the metal’s fluidity; however, adding more than a certain amount leads to a decrease in fluidity. The best result was observed when 0.6% aluminum was added. At this concentration, the surface tension of the metal decreased, the fluidity improved, and the complex-shaped parts of the mold were completely filled.
Keywords: 65Г steel, fluidity, aluminum, induction furnace, foundry, alloy, sand-clay mold, melting, metal composition, resource efficiency.